With mornefull musique : funeral elegies in early modern England - Grapes, K. Dawn (Music in Britain, 1600-2000 ;, 2018)
"This book looks at the musical culture of death in early modern England. In particular, it examines musical funeral elegies and the people related to commemorative tribute - the departed, the composer, potential patrons, and friends and family of the deceased - to determine the place these musical-poetic texts held in a society in which issues of death were discussed regularly, producing a constant, pervasive shadow over everyday life. The composition of these songs reached a peak at the end of the sixteenth and the beginning of the seventeenth centuries. Thomas Weelkes and Thomas Morley both composed musical elegies, as did William Byrd, Thomas Campion, John Coprario, and many others. Like the literary genre from which these musical gems emerged, there was wide variety in form, style, length, and vocabulary used. Embedded within them are clear messages regarding the social expectations, patronage traditions, and class hierarchy of late Elizabethan and early Jacobean England. En masse, they offer a glimpse into the complex relationship that existed between those who died, those who grieved, and attitudes toward both death and life."